2014
DOI: 10.2217/bmm.14.79
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Severity of Ureteropelvic Junction Obstruction Using Urinary Epidermal Growth Factor and Kidney Injury Molecule 1 levels

Abstract: Evaluation of the urinary KIM-1:Cr ratio may help identify neonates with severe obstructive hydronephrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Out of the 38 studies included in this systematic review, all (100%) searched for urine biomarkers and 5 (13.2%) (7,12,18,22,34), included also serum samples. Thirty-two (84.2%) studies considered only patients with unilateral PUJO while 6 (15.8%) included also patients with bilateral obstruction (5,6,20,21,33,35). The quantitative urine protein analysis was performed using commercially available human sandwich enzyme-linked immunosorbent assay (ELISA) kits in 32 (84.2%) studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 38 studies included in this systematic review, all (100%) searched for urine biomarkers and 5 (13.2%) (7,12,18,22,34), included also serum samples. Thirty-two (84.2%) studies considered only patients with unilateral PUJO while 6 (15.8%) included also patients with bilateral obstruction (5,6,20,21,33,35). The quantitative urine protein analysis was performed using commercially available human sandwich enzyme-linked immunosorbent assay (ELISA) kits in 32 (84.2%) studies.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen (36.8%) studies compared patients undergoing pyeloplasty [surgical group (SG)] with patients with mild non-obstructive dilatation not requiring surgery [non-surgical group (NSG)] and healthy children [reference group (RG)] (9,10, [14][15][16][17][18]20,22,27,29,[31][32][33]. Seven (18.4%) articles analysed urine biomarker concentrations in patients undergoing surgery (SG) and related them with patients conservatively treated (NSG) (6,19,21,28,36,37,41). Thirteen (34.2%) studies reported the comparison between surgical patients (SG) and healthy subjects (RG) (8,11,13,(24)(25)(26)30,34,35,(38)(39)(40)42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of urinary KIM-1 excretion as a new early biomarker of ON in patients with HN was reported by several recent studies [ 21 , 22 , 25 , 29 , 30 ]. However, in the study by Noyan et al [ 20 ], hydronephrotic children with kidney dysfunction were not characterized by increased urinary KIM-1 excretion.…”
Section: Discussionmentioning
confidence: 96%
“…Immortalized human renal tubular epithelial cells (HKC) were cultured at 37 °C with humidified atmosphere of 5 % CO 2 in DMEM/F12 supplemented with 10 % fetal bovine serum (FBS) and 2 ng/mL mouse epidermal growth factor and were seeded into 96-well culture plates (Corning, Schiphol-Rijk, The Netherlands) for 24 h. Subconfluent cells (culture surface covering nearly 70 %) were then exposed to various AMB or AMB formulation concentrations (1.0–10.0 μM). As kidney injury molecule-1 (KIM-1) and type I transmembrane glycoprotein neutrophil gelatinase-associated lipocalin (NGAL) have been reported to correlate with proximal tubular injury [17, 18], the cytotoxicity was measured periodically by measuring KIM-1 and NGAL using immunofluorescence, WB, and RT-PCR methods to determine early damage caused by exposure to AMB and AMB formulations. The prime set for NGAL was forward, 5′-TCA CCT CCG TCC TGT TTA G-3′ and reverse, 5′-CTC CTT GGT TCT CCC GTA-3′, and that for KIM-1 was forward, 5′-ACTCCTGCAGACTGGAATGG-3′ and reverse, 5′-CAAAGCTCAGAGAGCCCATC-3′.…”
Section: Methodsmentioning
confidence: 99%